Kepemimpinan Transformasional Kepala Madrasah Dalam Meningkatkan Profesionalisme Pendidik di SMP BP Gresik - Rosyidi, Muh. Hasyim (Mudir : Jurnal Manajemen Pendidikan, 2023)
The administration of the madrasa head in expanding educator impressive skill incorporates: a) The idealized influence element, which includes: The madrasa head constructs the responsibility of every educator to work on their skill, has thoughts in satisfying learning support, makes RKM and orders programs then disperses them, conveys the vision and mission of the madrasa. b) The element of inspirational motivation, specifically: The madrasa's principal always inspires, motivates, and provides excellent examples. c) The scholarly excitement part, specifically: Every issue is communicated to the teacher by the head of the madrasa, either in person or through meetings, and the teacher is always included in seminars and workshops. d) The factor of individual consideration, which includes: The head of the madrasa always listens to teachers' ideas and comes up with solutions, always rewards outstanding teachers, and places teachers based on their interests, skills, and abilities. The supporting variables for the groundbreaking authority of the madrasa head in expanding educator amazing skill are: a) The capacity of the madrasa head to prepare educators. b) The teacher has the confidence of the madrasa's principal. c) Monetary and supporting offices. d) The top of the madrasah who gives inspiration and backing to instructors. In the mean time, the repressing elements for the groundbreaking administration of the madrasah head in further developing educator amazing skill are: a) The head of the madrasah doesn't like the teacher's personality. b) The enthusiasm of various educators. c) The foundation's leaders did not necessarily agree with all of the madrasa's ideas. d) Older teachers who are unfamiliar with cutting-edge technology.